1999
DOI: 10.1148/radiology.212.3.r99se31699
|View full text |Cite
|
Sign up to set email alerts
|

Glenohumeral Relationships during Physiologic Shoulder Motion and Stress Testing: Initial Experience with Open MR Imaging and Active Imaging-Plane Registration

Abstract: Dynamic MR imaging of the glenohumeral joint is possible over a wide range of physiologic motion in vertically open systems. Use of an MR tracking coil enabled accurate tracking of the anatomy of interest. These preliminary measurements of normal glenohumeral motion patterns begin to establish normal ranges of motion and constitute a necessary first step in characterizing pathologic motion in patients with common clinical problems such as instability and impingement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 13 publications
3
46
1
4
Order By: Relevance
“…Such evidence could be provided by percutaneous bone pins, 26 or using radiographic 18 or magnetic resonance imaging (MRI) techniques. 2,23 The use of skin markers to explore the effects of foot orthoses on patellofemoral joint kinematics is ill advised. Reinschmidt et al 26 have documented that such analyses result in errors ranging from 21% to 70% for the 3 planes of knee motion compared with knee kinematics documented with bone pin markers.…”
Section: Direct Evidence For Effects Of Foot Orthoses On Patellofemormentioning
confidence: 99%
“…Such evidence could be provided by percutaneous bone pins, 26 or using radiographic 18 or magnetic resonance imaging (MRI) techniques. 2,23 The use of skin markers to explore the effects of foot orthoses on patellofemoral joint kinematics is ill advised. Reinschmidt et al 26 have documented that such analyses result in errors ranging from 21% to 70% for the 3 planes of knee motion compared with knee kinematics documented with bone pin markers.…”
Section: Direct Evidence For Effects Of Foot Orthoses On Patellofemormentioning
confidence: 99%
“…However, accurate assessment of glenohumeral displacements remains difficult due to the lack of investigation tools that allow for direct tracking of glenohumeral motion in multiple functional positions. in vivo analysis of glenohumeral displacements in shoulder functional positions were presented in the literature using open magnetic resonance imaging (MRI) (Beaulieu et al, 1999;Graichen et al, 2000;Massimini et al, 2012;Sahara et al, 2007) or model-based fluoroscopy imaging systems (Bey et al, 2006;Boyer et al, 2008;Massimini et al, 2012;Nishinaka et al, 2008;Zhu et al, 2012). These methods first require a personalized 3D model reconstruction based on computed tomography (CT) scan (Bey et al, 2006;Nishinaka et al, 2008) or MRI (Boyer et al, 2008;Massimini et al, 2012;Zhu et al, 2012).…”
mentioning
confidence: 99%
“…These results indicated that muscular stabilization of the scapula with external loading increased in the healthy shoulders to provide a critical platform for upper extremity activity. Numerous other studies have also shown the humeral head moving to the glenoid center during elevation in healthy shoulders 7,9,13,14,[18][19][20][21] , in contrast, injured shoulders with diagnoses of cuff de ciency, instability, and trauma exhibit humeral translation away from the glenoid center 7, 9, 18-22 .…”
Section: Discussionmentioning
confidence: 99%